Implementasi Keijakan Pemerintah Mendorong Pelaksanaan Keluarga Berencana (KB) - Lehona Simanjuntak; Putri Handayani; Hanna Iazzati Ar Raudah; Julia Ivana (Jurnal Multidisiplin Dehasen (MUDE), 2023)
KB (Family Planning) is a big policy made by the government in the midst of society, becoming one of the SDGs programs, namely population problems, in order to reduce the rate of growth and population explosion, namely by participating in the KB program. Family planning aims to form small, happy and prosperous families by means of regulating the birth of children, the ideal spacing and age of delivery, but without reducing a person's right to have children, according to the mandate of Law no. 52 of 2009 concerning population development and family development. This study aims to find out how the implementation of government policies in encouraging the implementation of the Family Planning (KB) program in the city of Medan, what factors are inhibiting and supporting the implementation of the Family Planning program, and benchmarks for the success of government policies in the Family Planning program. The method used is a qualitative descriptive research method using a literature study and an analysis of the issues being raised using a case study approach. The results of this study are that overall the implementation of the family planning program in the city of Medan has been going well, but in terms of disposition, namely the strong commitment and honesty of the family planning program health workers is needed so that the goals and objectives of the program run as expected. health workers are trained and skilled in providing family planning services, the available facilities are good. Then SOPs have been implemented by policy implementers in providing contraceptive services in family planning programs in Medan City Family Planning (PLKB). Researchers also provide recommendations for health workers who provide family planning services so they can better understand the SOP for family planning services properly and comprehensively and implement them consistently, in order to increase active family planning participants in the community in Medan City.